2011
DOI: 10.1007/s00542-011-1300-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling laser induced lubricant depletion in heat-assisted-magnetic recording systems using a multiple-layered disk structure

Abstract: In this paper, we model the depletion of lubricant from a disk surface subject to heating by a scanning laser in a heat assisted magnetic recording (HAMR) system. A multi-layer disk structure is used consisting of the substrate (either glass or aluminum), the CoFe based soft magnetic under-layer, a Ru based intermediate layer, a CoCrPt based recording layer, the diamond-like-carbon layer, and the lubricant film. The thickness and material properties of the different layers are shown to play an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…From a slider-disk interface perspective, the thermal stress is expected to challenge the robustness of today's protective carbon and boundary lubricant films. Numerous studies have been spawned to answer the question of whether or not the current carbon and lubricant "tribological layers" can survive HAMR technology [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…From a slider-disk interface perspective, the thermal stress is expected to challenge the robustness of today's protective carbon and boundary lubricant films. Numerous studies have been spawned to answer the question of whether or not the current carbon and lubricant "tribological layers" can survive HAMR technology [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment indicated that there is promise for achieving 4-6 nm HMS in the long term. While advancements in HDI design could enable significant reduction in HMS, new recording schemes could add to the challenge due to new sources of HMS loss: heat assisted magnetic recording (HAMR) will experience effects of high temperature at the interface [28][29][30], and bitpatterned magnetic recording (BPR) could have issues with added disk topography that would add to the touchdown height [31][32][33][34].…”
Section: Definition Of the Head-media Spacing Componentsmentioning
confidence: 99%
“…Trough widths of only 20 and 50 nm are used which is close to the expected HAMR optical field [5][6][7][8][9][10]. Multiple troughs simulations utilize edge-to-edge separation distances of either 20 or 50 nm or equivalently, center-to-center trough separation distances of 40 or 100 nm, respectively.…”
Section: Simulation Methodsmentioning
confidence: 99%